Expression of Translation Initiation Factors eIF-4E and eIF-2α and a Potential Physiologic Role of Continuous Protein Synthesis in Human Platelets - Rosenwald, Igor B.; Pechet, Liberto; Han, Anping; Lu, Linrong; Pihan, German; Woda, Bruce; Chen, Jane-Jane; Szymanski, Irma (Thrombosis and Haemostasis, 2001)
It is generally believed that platelets do not have a functionally significant protein synthetic machinery. However, our analysis demonstrated that normal bone marrow megakaryocytes express high levels of translation initiation factors eIF-4E and eIF-2α and the expression of these protein synthesis initiation factors is continued in platelets (as determined by immunohistochemistry and Western blot analysis). Both eIF-4E and eIF-2α are key regulators of protein synthesis. The eIF-4E is a rate-limiting part of a multisubunit complex, eIF-4F, that binds to the 5’ cap structure present in virtually all eukaryotic mRNAs, and carries out transfer of mRNAs to ribosomes for translation. Translation initiation factor eIF-2α is also a rate-limiting protein which associates with two other proteins to form an eIF-2 initiation factor complex responsible for the transfer of initiator methionyl-tRNA to the 40S ribosomal subunit. We confirm that expression of eIF-4E and eIF-2α is biologically relevant in that platelets continue protein synthesis, albeit at a 16 times lower rate than WBC (as determined by 35S-labeled amino acid incorporation, SDS-PAGE and scintillation counting). Finally, we determined that protein synthesis inhibitors (puromycin and emetine) attenuate the platelet aggregation response to a combination of ADP and epinephrine, but potentiate the response to collagen. Our data are consistent with the existence of different signal transducing pathways mediating the response to ADP/epinephrine and collagen. We suggest that the ADP/epinephrine response is positively affected by continuously synthesized proteins, while the response to collagen is modulated by continuously produced inhibitory proteins. Taken together, our results suggest that continuous protein synthesis is important for platelet function and its role in platelet physiology and pathophysiology deserves further study.
Keywords: Platelets; megakaryocytes; translation initiation factors; protein synthesis; aggregation